FANCC Dutch founder mutation in a Mennonite family from Tamaulipas, México. Issue 6 (1st May 2019) - García‐de Teresa, Benilde; Frias, Sara; Molina, Bertha; Villarreal, María Teresa; Rodriguez, Alfredo; Carnevale, Alessandra; López‐Hernández, Gerardo; Vollbrechtshausen, Lilia; Olaya‐Vargas, Alberto; Torres, Leda
Abstract: Background: Fanconi anemia (FA) (OMIM #227650) is a rare hereditary disease characterized by genomic instability. The clinical phenotype involves malformations, bone marrow failure, and cancer predisposition. Genetic heterogeneity is a remarkable feature of FA; at least 22 FANC genes are known to cooperate in a unique FA/BRCA repair pathway. A common rule on the mutations found in these genes is allelic heterogeneity, except for mutations known to have arisen from a founder effect like the FANCC c.67delG in the Dutch Mennonite Community. Here, we present an 11‐year‐old male patient, member of the Mennonite Community of Tamaulipas México, with a clinical and cytogenetic diagnosis of FA. Method: Chromosome fragility test was performed in all siblings. Genomic DNA was obtained from peripheral blood samples. Sanger sequencing was used to identify the FANCC c.67delG mutation (NC_000009.11(NM_000136.2):c.67delG p.(Asp23IlefsTer23)) and its accompanying haplotype. Results: The FANCC c.67delG mutation in 13 members of his family confirmed a FA diagnosis in two of his siblings and identified heterozygous carriers. Haplotype analysis supports that in this family, FA is caused by the founder mutation that initially appeared in Mennonite Dutch and followed this population's migrations through Canada and further to Mexico. Conclusion: The identification of the FANCC c.67delG mutation in this family not only allows proper genetic counseling, but it also grants the possibility to raise awareness of FA risk among the Mennonite community living in Mexico. Abstract : The identification of the FANCC c.67delG founder mutation in a Mennonite family from Tamaulipas, not only allows proper genetic counseling, but it also grants the possibility to raise awareness of FA risk among the Mennonite community living in Mexico.